ALA filing rules (American Library Association ChicagoUS, 2002)
Set of filing rules developed by members of the Filing Committee of the Resources and Technical Services Division (RTSD) of the the American Library Association (ALA). The rules are intended to be applicable to the arrangement of bibliographic regards regardless of the rules by which the records have been formulated.
Keywords: FILING